2020
DOI: 10.1007/s42995-020-00040-4
|View full text |Cite
|
Sign up to set email alerts
|

Colonization features of marine biofilm-dwelling protozoa in Chinese coastal waters of the Yellow Sea

Abstract: Colonization features of biofilm-dwelling protozoa, especially ciliates, are routinely used as a useful tool for marine bioassessment. In this review, we summarize some of these features to develop an optimal sampling strategy for using biofilmdwelling protozoa as bioindicators of marine water quality. We focus on the utility of: (1) diversity indices to analyze the colonization features of biofilm-dwelling protozoa for monitoring marine water quality; (2) MacArthur-Wilson and logistic equation models to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…This provided a more detailed insight into the dynamics of periphytic ciliates and revealed the prevalence of diverse taxonomic and functional groups over the course of colonization process. Seasonality of periphytic communities in temperate regions has been extensively studied (Sigee, 2005;Mora-Gómez et al, 2016), and seasonal shifts in community structure and dynamics have also been found for periphytic ciliates (Safi et al, 2014;Neury-Ormanni et al, 2020;Sikder et al, 2020). In this study, the taxonomic composition of ciliate communities significantly differed between the spring and summer seasons, confirming that seasonality strongly influences the ciliate colonization process.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This provided a more detailed insight into the dynamics of periphytic ciliates and revealed the prevalence of diverse taxonomic and functional groups over the course of colonization process. Seasonality of periphytic communities in temperate regions has been extensively studied (Sigee, 2005;Mora-Gómez et al, 2016), and seasonal shifts in community structure and dynamics have also been found for periphytic ciliates (Safi et al, 2014;Neury-Ormanni et al, 2020;Sikder et al, 2020). In this study, the taxonomic composition of ciliate communities significantly differed between the spring and summer seasons, confirming that seasonality strongly influences the ciliate colonization process.…”
Section: Discussionsupporting
confidence: 76%
“…The development and biological composition of periphytic communities is strongly influenced by environmental conditions, including factors such as light intensity, hydrology, water chemistry, macrophytes, planktonic communities and grazing pressure (Arndt et al, 2003;Liboriussen, 2003;Sigee, 2005;Vermaat, 2005). In temperate lakes, climate is another important factor for periphytic communities, and seasonal variations in environmental conditions (especially light and temperature) can lead to differences in the composition of periphytic phagotrophic protists, including composition of ciliate species (Arndt et al, 2003;Früh et al, 2011;Neury-Ormanni et al, 2020;Sikder et al, 2020). An increase in water temperature leads to an acceleration in ciliate growth rate and colonization, but this is also strongly dependent on resource availability (Norf et al, 2007(Norf et al, , 2009bFrüh et al, 2011;Villanueva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Protozoans represent an important biotic component in the aquatic ecosystem, particularly ciliates, which act as predators of bacteria, provide nutrition for organisms at higher trophic levels (Sikder et al, 2020). In addition, they increase mineralization and make nutrients more available to other organisms (Vickerman, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Uher et al (2005) found no connection between substrate type and algal communities on stone in southeastern Spain. Previous studies of microbial biofilms mostly concentrated on a single type of aquatic environment such as lakes ( Xu et al, 2005 ; Jiang et al, 2007 ) or coastal seas ( Xu et al, 2009 ; Abdullah Al et al, 2018 ; Sikder and Xu, 2020 ; Sikder et al, 2020 ). Few studies have compared microeukaryotic community assemblies on substrates in different aquatic fluctuating conditions ( Battin et al, 2003 ; Besemer et al, 2007 ), even though it is recognized that current and tide play important role in microeukaryotic colonization ( Xu et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%